2022
DOI: 10.3389/fcvm.2022.995367
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cardiac imaging assessment of epicardial adipose tissue after a first episode of myocardial infarction

Abstract: BackgroundOver the past years, information about the crosstalk between the epicardial adipose tissue (EAT) and the cardiovascular system has emerged. Notably, in the context of acute myocardial infarction (AMI), EAT might have a potential role in the pathophysiology of ventricular structural changes and function, and the clinical evolution of patients. This study aims to assess the impact of EAT on morpho-functional changes in the left ventricle (LV) and the outcome of patients after an AMI.MethodsWe studied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The relationship between pre-existing EAT at the time of acute coronary occlusion and resulting IS has been controversial. Concurring with our results, Islas et al [15], Mohamed et al [16], Fisser et al [11], and Toya et al [17]. reported larger infarctions in patients with high EAT; however, Bière et al [18] and Gohbara et al [12] detected the opposite.…”
Section: Eat and Issupporting
confidence: 89%
See 1 more Smart Citation
“…The relationship between pre-existing EAT at the time of acute coronary occlusion and resulting IS has been controversial. Concurring with our results, Islas et al [15], Mohamed et al [16], Fisser et al [11], and Toya et al [17]. reported larger infarctions in patients with high EAT; however, Bière et al [18] and Gohbara et al [12] detected the opposite.…”
Section: Eat and Issupporting
confidence: 89%
“…(ii) EAT is a biologically active tissue closely connected with the myocardium [5]. Parallel to the response detected in the myocardium itself, in the acute post-infarction period EAT can also undergo a deregulated pro-inflammatory response which can ultimately contribute to an undesirable expansion of structural damage [4][5][6]15].…”
Section: Eat and Ismentioning
confidence: 99%
“…The EAT thickness measured in transthoracic echocardiography in subjects with MI corresponded positively with ST-segment resolution, reduction in LVEF, reduction in LV end-diastolic and end-systolic volume, and larger infarct size [171,179]. Furthermore, thick EAT was correlated with the presence of coronary collateral vessels (CCVs) in patients presenting with ACS.…”
Section: Eat Thicknessmentioning
confidence: 88%
“…It also appeared to be an independent risk factor of NSTEMI, unstable angina pectoris [167], and restenosis after PCI [168]. Additionally, the EAT thickness in echocardiography occurred to be significantly predictive of adverse cardiovascular events in patients presenting with AF [169] and ACS during short-term and long-term follow-up [170,171]. Moreover, individuals with high echocardiographic EAT thickness were more likely to require target vessel revascularization.…”
Section: Eat Thicknessmentioning
confidence: 94%
“…reported that acute myocardial infarction patients with EAT >4 mm have worse left ventricular systolic function and have large infarct size. EAT >4 mm is an independent predictor of major adverse cardiovascular events at 5-year follow-up ( 30 ).…”
Section: Cardiac Imaging Of Eatmentioning
confidence: 99%